Strengthening Soil Databases for Climate Change and Food Security Modeling Applications - Chaves, B.; Hoogenboom, Gerrit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Climate change is a hazard to the food security of a growing world population since it affects agriculture and likewise, agriculture and natural resource management affect the climate system. The relationships between all these factors including polices, political conditions, economical management and pest and diseases, and how they interact are not currently well-understood, nor are the advantages and disadvantages of different responses to climate change. In the face of climate change it is important to integrate knowledge about it to generate realistic solutions for agriculture, and food security in a meaningful and innovative way. Research in this topic has focused on addressing the needs for methods, models, databases and system metrics aimed at enhanced assessment and improved methodologies for the impact of climate change on agricultural systems and the development of different policy and program interventions to foster adaptation and mitigation in terms of poverty alleviation, food security and environmental health. This work should be in a framework and set of modeling tools and databases to analyze the implications of human responses to the climate challenge in terms of regional food security and the preservation of important ecosystem services, upon which the long-term sustainability of global agriculture must be based.